2007
DOI: 10.1002/pmic.200700582
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of annexin a1 induced by terephthalic acid calculi in rat bladder cancer

Abstract: Prolonged cell proliferation in response to irritation by bladder calculi can evoke malignant transformation of the urothelium. However, the molecular mechanisms responsible for calculi-associated bladder carcinogenesis are unknown. We compared the protein expression pattern of rat bladder transitional cell carcinomas (TCCs) induced by terephthalic acid with that of normal bladder tissues using 2-DE. Comparative analysis of the respective spot patterns on 2-DE showed 146 spots that were markedly changed in TCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Evidence for this lies in the clear observations that its expression is in a tumor-specific manner. It has been reported that annexin A1 is up-regulated in hepatocellular carcinoma (de Coupade et al, 2000), bladder cancer (Cui et al, 2007), larynx cancer (Silistino-Souza et al, 2007), human breast cancer (Kang et al, 2012) and pituitary adenoma (Mulla et al, 2004), while it is absent or down-regulated in human esophageal squamous cell carcinoma (Liu et al, 2003), oral squamous-cell carcinoma (Nomura et al, 2009), prostate cancers (Silistino-Souza et al, 2007) head and neck cancers (Garcia Pedrero et al, 2004), intestinal-type sinonasal adenocarcinoma (Rodrigo et al, 2011), B-cell non-Hodgkin's lymphomas (Vishwanatha et al, 2004), thyroid cancers (Petrella et al, 2006) and endometrial carcinoma (Da et al, 2001). In our study, we found that annexin A1 was significantly overexpressed in PDAC tissues by real-time RT-PCR, Western blot and immunohistochemistry, which was consistent with the early study of annexin A1 expression in pancreatic cancer (Bai et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for this lies in the clear observations that its expression is in a tumor-specific manner. It has been reported that annexin A1 is up-regulated in hepatocellular carcinoma (de Coupade et al, 2000), bladder cancer (Cui et al, 2007), larynx cancer (Silistino-Souza et al, 2007), human breast cancer (Kang et al, 2012) and pituitary adenoma (Mulla et al, 2004), while it is absent or down-regulated in human esophageal squamous cell carcinoma (Liu et al, 2003), oral squamous-cell carcinoma (Nomura et al, 2009), prostate cancers (Silistino-Souza et al, 2007) head and neck cancers (Garcia Pedrero et al, 2004), intestinal-type sinonasal adenocarcinoma (Rodrigo et al, 2011), B-cell non-Hodgkin's lymphomas (Vishwanatha et al, 2004), thyroid cancers (Petrella et al, 2006) and endometrial carcinoma (Da et al, 2001). In our study, we found that annexin A1 was significantly overexpressed in PDAC tissues by real-time RT-PCR, Western blot and immunohistochemistry, which was consistent with the early study of annexin A1 expression in pancreatic cancer (Bai et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this interpretation, some types of cancers such as esophageal carcinoma and prostate cancer have decreased levels of annexin A1 (Lim & Pervaiz, 2007). However, recent pathohistochemical evidence with esophageal carcinoma and neck squamous carcinoma suggests that such down-regulation of annexin A1 is partially attributed to nuclear translocation, and the nuclear translocation of annexin A1 is facilitated by tyrosine and/or serine phosphorylation and Ca 2+ signals as well as by oxidative stress (Rhee et al, 2000;Kim et al, 2003;Liu et al, 2003;Cui et al, 2007;Lin et al, 2008). The presence of annexin A1 in nuclei is now proposed to be a poor prognostic marker of squamous cancer or to be associated with malignancy of gastric carcinoma, while changes in cellular expression of annexin A1 may not be involved in tumorigenesis (Lin et al, 2008;Zhu et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
“…In addition, the product of this gene is a calcium-binding protein, which can influence the concentration of cytoplasmic free Ca 2+ , and is involved in mitochondria-mediated apoptosis and many other cellular signal communications in the carcinogenesis [29] . Recently, studies have shown that some calcium-binding proteins play an important role in carcinogenesis [30,31] . For example, the overexpression of calcium-binding protein S100A4 can induce the metastatic phenotype in an orthotopic model of bladder cancer, in which a cell line originally derived from a carcinogen-induced rat bladder tumor is injected into the muscular wall of syngeneic rats.…”
Section: Discussionmentioning
confidence: 99%